A Health Technology Assessment of Transient Elastography in Adult Liver Disease - Rodney Steadman; Robert P Myers; Laura Leggett; Diane Lorenzetti; Tom Noseworthy; Sarah Rose; Lloyd Sutherland; Fiona Clement (Canadian Journal of Gastroenterology)
BACKGROUND: An estimated one in 10 Canadians have some form of liver disease. The reference standard for staging and monitoring liver fibrosis is percutaneous liver biopsy – an invasive procedure associated with risks and complications. Transient elastography (TE) represents a noninvasive, ultrasound-based alternative.